Using Influence Matrices as a Design and Analysis Tool for Adaptive Truss and Beam Structures - Steffen, Simon; Weidner, Stefanie; Blandini, Lucio; Sobek, Werner (Frontiers in Built Environment, 2020)
Due to the already high and still increasing resource consumption of the building industry, the imminent scarcity of certain building materials and the occurring climate change, new resource- and emission-efficient building technologies need to be developed. This need for new technologies is further amplified by the continuing growth of the human population. One possible solution proposed by researchers at the University of Stuttgart, and which is currently further examined in the context of the Collaborative Research Centre (SFB) 1244 Adaptive Skins and Structures for the Built Environment of Tomorrow is that of adaptivity. The integration of sensors, actuators, and a control unit enables structures to react specifically to external loads, when needed (e.g., in the case of high but rare loads). For example, adaptivity in load-bearing structures allows for a reduction of deflections or a homogenization of stresses. This in its turn allows for ultra-lightweight structures with significantly reduced material consumption and emissions. To reach ultra-lightweight structures, i.e., adaptive load-bearing structures, two key questions need to be answered. First, the question of optimal actuator placement and, second, which type of typology (truss, frame, etc.) is most effective. One approach for finding the optimal configuration is that of the so-called influence matrices. Influence matrices, as introduced in this paper, are a type of sensitivity matrix, which describe how and to which extend various properties of a given load-bearing structure can be influenced by different types of actuation principles. The method of influence matrices is exemplified by a series of studies on different configurations of a truss structure.